ANALISIS NILAI PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR (Studi Nilai Perusahaan pada 10 Perusahaan Manufaktur BEI) - Supriandi Supriandi; Yusuf Iskandar (Referensi : Jurnal Ilmu Manajemen dan Akuntansi, 2021)
Every company definitely wanted its business to run smoothly and can even develop and achieved company goals in business competition, in this era of globalization, companies must realized that competition would be very fierce and need speed because high aset levels woulf not guarantee a company can. One of the ways to survived was to maximize Firm Value. This research was a quantitative descriptive study designed to collected information about firm value in 10 manufacturing companies listed on the Indonesia Stock Exchange (IDX) in the Pharmaceutical sub-sector. This study used secondary data taken in the 2015 to 2019 period. Based on the results showed that the pharmaceutical subsektor still has issuers that have company values below 1 and still have the company is in the category of undervalued company value.